A looking-glass for King-opposers, or, Twenty admirable examples of Gods severe justice and displeasure against the subscribers of the late engagement against our lawfull soveraign King Charles the II. and the whole House of Peers: in these words, I do declare and promise that I will be true and faithfull to the Common wealth of England ... Also against some of the judges of the late King in the high court of injustice. [electronic resource] : (1660)
Summary goes here